Análisis del ciclo de la moda a través del estudio del pantalón palazzo - Paredes Chérrez, Keyla Raquel (2024)
The fashion industry has experienced continuous changes over the past decades, characterized by trends that affect the fashion cycle. In previous decades, a fashion trend could last for several seasons, or even years. However, these days, trends change quickly, sometimes in a matter of weeks or even days. The present study focuses on analyzing the fashion cycle, focusing on various factors that affect said cycle, given that trends emerge and reappear at an increasingly accelerated rate, for this an exhaustive investigation is carried out through a specific garment: the palazzo pants. To achieve this objective, a qualitative investigation is carried out that covers both the documentary-bibliographic modality and field work. The latter includes semi-structured interviews with fashion experts and designers, as well as detailed observations on the evolution of palazzo pants from their appearance in the 1930s to the present day. As a result of this study, it was possible to identify through a timeline that the fashion cycle has been significantly shortened in recent decades. This acceleration is attributed to globalization, the impact of social networks and technological advances, which they have allowed a rapid dissemination of information, in addition, for several decades the palazzo pants had constant changes, influenced by both styles and the social context, influenced by both styles and the social context, instantly facilitating relevant changes in the market that is constantly changonga today